Robust visible-light photocatalytic H2 evolution on 2D RGO/Cd0.15Zn0.85In2S4–Ni2P hierarchitectures. Issue 13 (1st June 2022) - Lin, Haifeng; Sui, Xue; Wu, Jiakun; Shi, Qiqi; Chen, Hanchu; Wang, Hui; Li, Shaoxiang; Li, Yanyan; Wang, Lei; Tam, Kam Chiu
Abstract : Unique 2D ternary hierarchitectures constructed from reduced graphene oxide nanosheets grown with ultrathin Cd0.15 Zn0.85 In2 S4 nanosheets and Ni2 P nanoparticles exhibited an outstanding capability for visible-light photocatalytic H2 production. Abstract : Photocatalytic water-splitting to produce hydrogen (H2 ) is considered one of the most promising strategies to solve the increasing energy and environmental challenges facing humanity. However, the major obstacle is the lack of highly efficient photocatalysts with visible-light absorption capability and prominent charge transfer and separation. Herein, we developed for the first time an interface-engineered 2D hierarchitecture comprising ultrathin Cd-doped ZnIn2 S4 (Cd0.15 Zn0.85 In2 S4 ) nanosheets coupled with Ni2 P nanoparticles as a cocatalyst and reduced graphene oxide (RGO) nanosheets as an electron mediator. Under visible-light ( λ > 400 nm) irradiation, the RGO/Cd0.15 Zn0.85 In2 S4 –Ni2 P composite displayed an enhanced H2 evolution activity of 14.56 mmol h −1 g −1 that is 22 times that of pristine ZnIn2 S4, and much higher than those of RGO/Cd0.15 Zn0.85 In2 S4, Cd0.15 Zn0.85 In2 S4 –Ni2 P, Pt-loaded RGO/Cd0.15 Zn0.85 In2 S4, and many previously reported ZnIn2 S4 -based photocatalysts. Additionally, the RGO/Cd0.15 Zn0.85 In2 S4 –Ni2 P hybrids showed outstanding long time cycling stability. The excellent photocatalytic HER capability of our photocatalyst could be attributed to the enhanced light-harvesting capability of porous hierarchitectures, increased charge transfer and separation via the interface-engineered Schottky heterojunctions, and the many active sites of the Ni2 P cocatalyst. The synergistic cooperation of the cocatalyst and electron mediator in 2D nanostructures offers a promising approach to prepare efficient solar photocatalysts.